Comparison of clinical outcomes in STEMI patients treated with primary PCI according to day-time of medical attention and its relationship with circadian pattern. (15th April 2020) - Rodríguez-Arias, Juan J.; Ortega-Paz, Luis; Brugaletta, Salvatore; Freixa, Xavier; Masotti, Mónica; Regueiro, Ander; Ariza, Albert; Carrillo, Xavier; Lidon, Rosa-Maria; Garcia, Joan; Cardenas, Merida; Rojas, Sergio G.; et al.
Abstract: Objective: Relationship between STEMI time of presentation, its circadian pattern and cardiovascular outcomes is unclear. Our objective is to analyze clinical outcomes of STEMI according to time of presentation and circadian pattern. Methods: We analyzed data from patients treated within the regional STEMI Network from January 2010 to December 2015. On-hour group included patients treated between 8:00 h and 19:59 h on weekdays, the rest were catalogued as off-hour group. The primary endpoint was 1-year all-cause mortality. Secondary endpoints were 30-day all-cause mortality and in-hospital complications. Results: A total of 8608 patients were included, 44.1% in the on-hour group and 55.9% in the off-hour group. We observed a shorter patient delay and longer system delay in the off-hour group compared to on-hour group with no difference in total ischemic time. At 30-day and 1-year follow-up there were no differences in adjusted all-cause mortality between groups [OR 0.91 (CI95%: 0.73–1.12; p = 0.35) and OR 0.99 (CI95%: 0.83–1.17; p = 0.87), respectively]. A circadian pattern was observed between 9:00 am and 12:30 pm, with no differences in 30-day and 1-year mortality between patients included in this time interval [OR 1.02 (IC95%: 0.81–1.30; p = 0.85) and OR 1.12 (IC95%: 0.92–1.36; p = 0.25) respectively]. Conclusions: Off-hour STEMI presentation was associated with a shorter patient delay and longer system delay without an increase in total ischemic time. The off-hour presentation was not related to an increase in 1-year all-cause mortality when compared to on-hour. A circadian pattern was found, without differences in 30-day and 1-year mortality. Highlights: Off-hour treatment is associated with shorter system delay. On-hour treatment is associated with shorter patient delay. These differences are not related to any difference in all-cause mortality. A circadian pattern has been observed between 09:30 am and 12:30 pm. Not differences were found in all-cause mortality during the circadian time interval.